Inovasi Patty sandwich Dengan Proporsi Ikan Patin (Pangasius Sp) Dan Kelapa Muda Sangrai Dengan Penambahan Puree Daun Semanggi - Adam Ardhul Jadid Rizki Dwi Putra; Any Sutiyadiningsih; Lilis Sulandari; Ita Fatkhur Romadhoni (Journal of Creative Student Research, 2023)
Patty sandwich is a processed product made from catfish, coconut runch, and clover leaf puree which is formed into a square measuring 8 x 8 cm with a thickness of 1 cm which is used as a filling for white bread or sandwiches. The aims of this study were 1) to determine the sensory quality of patty sandwiches with the proportion of catfish and roasted young coconut with the addition of clover leaf puree, 2) to determine the nutritional content per 100 g of patty sandwich with the proportion of catfish and roasted young coconut with the addition of clover leaf puree, and 3) find out the cost of raw materials for patty sandwiches. This type of research is an experiment. The data collection technique used meted observation by means of a sensory quality test on 35 panelists (5 expert panelists and 30 semi-trained) who were assisted by a line scale observation sheet (0-15 cm). The independent variables in this study were the proportions of roasted catfish and young coconut (60% : 40%, 70% : 30%, and 80% : 20%) and the addition of cloverleaf puree (5% and 10%). The dependent variable of the research is sensory quality including shape, color, texture, aroma, and taste. The control variables in this study include the types of materials, equipment, and processing techniques. Data analysis used double anova test and Duncan's further test. The results showed 1) there was an effect of adding cloverleaf puree on shape, color, and taste, 2) there was an effect on the proportion of catfish and roasted young coconut on texture, aroma and taste, 3) there was no effect of the proportion interaction with the addition on the sensory quality of the patty sandwich on shape, color, texture, aroma, and taste.